AI-Driven Plugin Architecture for Enterprise Integration - Sneh Lata (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This journal outlines the strategic development, implementation, and optimization of AI-driven plugin systems for enterprise integration. Drawing upon real-world experience in managing end- to-end AI transformation initiatives, the document presents a modular, scalable approach to re - architecting legacy and modern enterprise software systems. It focuses on delivering automation, intelligence, and customizability through machine learning (ML) and natural language processing (NLP) technologies embedded into plugin frameworks.
Keywords: AI Integration; Plugin Architecture; Enterprise Automation; Machine Learning and NLP